Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding. Issue 12 (4th December 2013) - Nomura, Daiki; Granskog, Mats A.; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen
Abstract : [1] In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface ( F flood ) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m −2 d −1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow‐air surface ( F snow ) and bare ice surface ( F ice ). The F snow / F flood ratio decreased with increasing water equivalent of snow and superimposed‐ice, suggesting that the properties of snow and superimposed‐ice formation affect the magnitude of the CO2 flux. The F snow / F flood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed‐ice. Hence, snow cover properties and superimposed‐ice play an important role in the CO2 fluxes across the sea ice‐snow‐atmosphere interface. Key Points: Melting sea ice acts as a sink for atmospheric CO2 The magnitude of the CO2 flux depends on the properties of ice surface The presence of snow and superimposed‐ice reduced the potential CO2 flux